Strategies on Increasing Brand Awareness in Faculty of Architecture and Design (FAD) UPN “Veteran” Jawa Timur - Sri Suryani Yuprapti W; Dyan Agustin; Wiwik Dwi Susanti; Aris Sutedja (Nusantara Science and Technology Proceedings)
College nowadays should be able to increase brand awareness or so that the image of the college can be embedded in the minds of the community. The establishment and improvement of brand awareness is an effort to improve the quality, especially a Faculty in a college. The strategies used for the improvement are influenced by student targets, competitors and credibility. The method used is to conduct FAD SWOT analysis as the foundation of branding strategy. The result of this research is that FAD as a new faculty has strong character of arts based on state defense because it consists of two study programs that have high art content that is Department of Architecture and Department of Visual Communication Design.